Review of medical microbiology and immunology - Levinson, Warren (McGraw-Hill Medical, 2012)
"This book is a concise review of the medically important aspects of microbiology and immunology. It covers both the basic and clinical aspects of bacteriology, virology, mycology, parasitology, and immunology. Its two major aims are (1) to assist those who are preparing for the USMLE (National Boards) and (2) to provide students who are currently taking medical microbiology courses with a brief and up-to-date source of information"--Provided by publisher
"A Lange medical book."
Includes index
Keywords: Allergy and Immunology -- Examination Questions; Allergy and Immunology -- Outlines; Clinical & internal medicine; Immunologic Techniques -- Examination Questions; Immunologic Techniques -- Outlines; Medical microbiology -- Textbooks; Microbiology -- Examination Questions; Microbiology -- Handbooks; Microbiology -- Outlines; Microbiology -- Questions